Penerapan Perilaku CERDIK dan Pemeriksaan Gula Darah dalam Pencegahan dan Pengendalian Penyakit Diabetes Mellitus (DM) pada Masyarakat - Rezekiyah, Sholeha; Lestari, Wuni Sri (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
DM is a disease caused by high blood sugar levels due to disorders of the pancreas and insulin. However, 1 in 2 people with DM do not know that they have DM. To control DM, the Ministry of Health itself has established 13,500 Integrated Development Posts (Posbindu) to facilitate citizens' access to early detection of DM. Apart from that, the Minister of Health appealed to the public to take CERDIK action, in the form of diligent physical activity, a healthy and balanced diet, adequate rest and managing stress.The aim of this Community Service is to increase the implementation of CERDIK action as an effort to prevent and control DM disease in the Penyengat Olak Village community. The activities carried out were in the form of counseling about diabetes mellitus, CERDIK action and blood glucose checks in the Penyengat Olak Village community. The results of the activity show that public knowledge about Diabetes Mellitus has increased, where before the outreach the public only knew that Diabetes existed but did not know how it could be affected and how to treat, prevent and control the disease, after the outreach the public became more knowledgeable about Diabetes Mellitus. The community also did not know that the CERDIK action program existed, after the activities the community learned that there was a CERDIK action to control DM disease. The results of blood glucose examinations show that the majority of people have normal blood glucose levels.